‘Like touching climate change’: glaciers reveal records of the way the world was - Giuffrida, Angela (The Guardian, 2025)
Scientists drill for ice cores containing information on preindustrial pollutants, but they are in a race against time
Keywords: Climate crisis; Environment; Glaciers; Polar regions